Bromeliad-living spiders improve host plant nutrition and growth - Romero, G. Q.; Mazzafera, P.; Vasconcellos-Neto, J.; Trivelin, PCO (Ecological Soc Amer, 2006)
Although bromeliads are believed to obtain nutrients from debris deposited by animals in their rosettes, there is little evidence to support this assumption. Using stable isotope methods, we found that the Neotropical jumping spider Psecas chapoda (Salticidae), which lives strictly associated with the terrestrial bromeliad Bromelia balansae, contributed 18% of the total nitrogen of its host plant in a greenhouse experiment. In a one-year field experiment, plants with spiders produced leaves 15% longer than plants from which the spiders were excluded. This is the first study to show nutrient provisioning in a spider-plant system. Because several animal species live strictly associated with bromeliad rosettes, this type of facultative mutualism involving the Bromeliaceac may be more common than previously thought.
Keywords: animal-plant interaction; Bromelia balansae; Bromeliaceae; digestive mutualism; jumping spider; nitrogen fluxes; nutrient provisioning; Psecas chapoda; Salticidae; spider-plant mutualism; stable isotope N-15